Predicting Difficult Bile Duct Cannulation: Accuracy of Endoscopic Visualization of the Papilla to Predict Cannulation Difficulty - Azar, Riad R. (2010)
Predicting difficult cannulation of the common bile duct (CBD) may impact the approach to CBD cannulation.